The role of the striatin family proteins in hippo signaling and cellular regulation - Yarden Shor-Nareznoy; Michal Caspi; Yan Lender; Amnon Wittenstein; Arad Soffer; Hanin Elias; Natalie Zelikson; Rana Masri; Rose Jbara; David C. Pallas; Metsada Pasmanik-Chor; Chen Luxenburg; et al. (Cell & Bioscience)
Abstract The striatin family proteins, striatin, SG2NA, and zinedin, belong to the calmodulin-binding WD-40 repeat protein group and are components of the striatin interacting phosphatase and kinase (STRIPAK) complex. These proteins are known for their roles as scaffold proteins, facilitating various cellular pathways, and regulating cell–cell interactions and signaling mechanisms. The observation that Striatin is expressed in cell junctions, suggests a potential role in maintaining cell integrity and communication. Here, we used shRNA technology to examine the biological significance of the striatin family proteins. This approach allowed us to modulate their expression levels and observe the effects on cellular processes. Our results suggest that the striatin family members affect the Hippo signaling pathway by protecting phosphorylated YAP (pYAP) from proteasomal degradation, thus decreasing the expression of Hippo target genes. This regulation impacts key cellular processes, such as cell migration and proliferation. RNA sequencing analyses of keratinocytes and fibroblasts depleted of striatin proteins enabled the identification of novel gene sets affected by the modulation of striatin expression and provided insights into the broader impact of striatin proteins and their roles in various cellular pathways.